Species composition and distribution of Family Spionidaev (ANNELIDA POLYCHAETA) in the Calamianes Group of Islands, Northern Palawan. - Palla, Rocille Quilantang (2005.)
The species composition and distribution of family spionidae (Annelida:Polychaeta) in the Calamianes group of Islands, Northern Palawan was investigated in this study. A total of 96 individuals divided into 14 species belong to family Spionidae, with an over-all mean density of 48.82 ind . m-2 and a range of 10.68 . m-2 to 288. 36 ind . m-2. The three most abundant species were Spiophanes soederstromi (29.17 percent), spio filicornis (23.97 percent) and Prionospio pinnata (17.71 percent). when group by genus, Prionospio and Spiophanes were the most abundant genera (30.21 percent)., A geographical pattern was seen in the distribution of the family wherein specimens were found only in the peripheral stations while there was an absence of specimen in the 9 centrally located stations. The Q-mode cluster analysis revealed that the distribution of the family Spionodae in the 21 stations is divided into 2 major clusters and 3 station groups. The 9 centrally located stations were Classified as Cluster 1. The peripheral stations were classified as Cluster 2 that is further divided into Cluster 2a and cluster 2b. The absence of specimens in the 9 centrally located stations (Cluster 1) may be attributed to the high percentage of sand and a very low silt-clay component . correlation analysis showed that the density of spionids is negatively related to percent sand positively related to percent mud. The sediment regime of the area was found to be poorly or very poorly sorted , with sorting index values ranging from 3.99 in station 22A to 1.84 in station 12. this could indicate low wave and current activity in the Calamianes group of islands. Sorting index was positively correlated for most genera (namely, Rhyncospio, Spiophanes, Spio and Polydora). Midphi was also positively correlated to all genera except Polydora. Members of the family primarily rely on sediment particles they can ingest, for nutrients.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Annelida Polychaeta